Similarities and differences between Turkic languages and comparative methods in teaching them - Zhumakunova, Gyulzura (The New Research of Tuva, 2018)
Turkic languages are cognate language which stem back to the single ancestor – Proto-Turkic language. In the course of long and convoluted history of Turkic-speaking peoples, all of their languages suffered various degrees of change on every level of its structure – in phonemes, morphemes, vocabulary and syntax. At the same time, all of these languages have preserved some of their common features which link them to their ancestor tongue. In this article, the author, from her long experience of teaching Kyrgyz at Ankara University, explains her vision of teaching Turkic languages in general and describes the methods and approaches which she deems helpful in successful teaching on university level.In teaching a Turkic language, the main objective is not to focus on language study as such, but take a breathtaking journey along the hidden paths of one’s mother tongue and get to understand it in a more profound way, in its historical retrospective. Turkic languages have always attracted linguists and were in the focus of their studies. Getting acquainted with various linguistic theories and the works of prominent Turkologists, as seen from teaching practice, is also very helpful to shape an enduring interest in learning both the target language and first language more profoundly.We also have to take into account such extralinguistic factors as the objective of language study, friendliness of the environment and the demand for language in a given environment. The article examines these issues through the alphabets and their various uses among Turkic peoples. When setting up a language study program, it is also important to take into account how familiar students are with the target language.Overall, this new type of work required a fundamental study of methodological foundations of language teaching. New types of academic and learners’ dictionaries have to be prepared, as well as new textbooks to help students of a specific Turkic language.
Keywords: Turkic language; Turkic peoples; Kyrgyz language; problems of teaching language; Turkey; methods of teaching